Multiomics Approach Distinguishes SPTBN4 as a Key Molecule in Diagnosis, Prognosis, and Immune Suppression of Testicular Seminomas - Jianfeng Xiang; Yanjie Xiang; Qintao Ge; Yunhong Zhou; Hailiang Zhang; Wenhao Xu; Shifang Zhou; Liang Chen (International Journal of Genomics)
Conclusion: In conclusion, this multiomics study identifies SPTBN4 as a central biomarker in testicular seminomas, encompassing diagnostic, prognostic, and therapeutic dimensions. The integration of single-cell transcriptomics, hdWGCNA, and drug sensitivity analyses underscores the molecular complexity of seminomas and highlights the translational potential of SPTBN4 in guiding personalized treatment strategies. These findings provide a foundation for leveraging multiomics approaches to advance the clinical management of testicular seminomas and other heterogeneous malignancies.